2005
DOI: 10.1111/j.1442-2042.2005.01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimal invasiveness and effectivity of subinguinal microscopic varicocelectomy: a comparative study with retroperitoneal high and laparoscopic approaches

Abstract: Aim : The standard management of varicocele repair is the subject of ongoing controversy. We retrospectively evaluated three surgical methods of varicocele treatment to determine the minimally invasive and most effective procedure. Methods : We performed 144 varicocelectomies on infertile patients with left clinical varicocele. Of the patients, 50 were treated with retroperitoneal high ligation under lumbar anesthesia, 33 with laparoscopic ligation under general anesthesia, and 61 with subinguinal microscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 36 publications
2
57
2
3
Order By: Relevance
“…A future randomized study including the quantitative evaluation of the therapeutic physical changes is planned to further elucidate the dose-dependency between the three dosing groups. The average testosterone levels in the treatment groups reached around 700 ng/dL, which is comparable to the testosterone levels in normal males [9,10].…”
Section: Desired Clinical Effectssupporting
confidence: 52%
“…A future randomized study including the quantitative evaluation of the therapeutic physical changes is planned to further elucidate the dose-dependency between the three dosing groups. The average testosterone levels in the treatment groups reached around 700 ng/dL, which is comparable to the testosterone levels in normal males [9,10].…”
Section: Desired Clinical Effectssupporting
confidence: 52%
“…The standard management of varicocele repair is the subject of ongoing controversy. In a comparative study of three surgical methods of varicocele treatment Watanabe and colleagues (Watanabe et al, 2005) compared various minimally invasive method. They compared retroperitoneal high ligation under lumbar anesthesia, laparoscopic ligation under general anesthesia, and subinguinal microscopic ligation under local anesthesia.…”
Section: Varicocelectomymentioning
confidence: 99%
“…3,4 Other recent studies have shown that the prevalence of malfunction of one-way valves in the ISV increases by 10-15% for each decade of life. 5 Varicocele arises exclusively in humans, whose erect posture predisposes the valves to high gravitational forces. Quadrupeds do not require valves in their ISV to assist venous return.…”
Section: Editorial Comment To Umbilical Laparoendoscopic Single Site mentioning
confidence: 99%
“…1,2 However, a comparative study showed no superiority of laparoscopic varicocele ligation over the standard open subinguinal varicocelectomy with respect to operative time, postoperative pain, cost-effectiveness and complications. [5][6][7] Laparoendoscopic single site surgery (LESS) was introduced several years ago. LESS has been carried out successfully for laparoscopic nephrectomies, cholecystectomies and appendectomies.…”
Section: Introductionmentioning
confidence: 99%